1992
DOI: 10.1104/pp.100.3.1189
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Oxidative Burst in Phytoalexin Accumulation and the Hypersensitive Reaction

Abstract: The role of the oxidative burst, transient production of activated oxygen species such as H202 and superoxide (02)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 25 publications
3
40
1
Order By: Relevance
“…One of the reaction products formed by oxalate oxidase is H 2 O 2 , and the rapid release of H 2 O 2 has been reported to occur in several plants upon treatment with an elicitor of plant defense responses (Apostol et al, 1989;Devlin and Gustine, 1992;Niirnberger et al, 1994). Moreover, Chen et al (1993) recently demonstrated that salicylic acid, a natural signal molecule for the activation of plant defense responses, inhibits a catalase isoenzyme in tobacco leaves, leading to increased levels of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the reaction products formed by oxalate oxidase is H 2 O 2 , and the rapid release of H 2 O 2 has been reported to occur in several plants upon treatment with an elicitor of plant defense responses (Apostol et al, 1989;Devlin and Gustine, 1992;Niirnberger et al, 1994). Moreover, Chen et al (1993) recently demonstrated that salicylic acid, a natural signal molecule for the activation of plant defense responses, inhibits a catalase isoenzyme in tobacco leaves, leading to increased levels of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…These AOS include superoxide (O[-), hydrogen peroxid,: (H202), and the hydroxyl radical (OH') [1,2]. The signifivance of AOS acting as a signal towards host defense in plant-pathogen interactions has been demonstrated by HaO2.mediated oxidative cross-linking of the plant cell wall during HR [3,4], phytoalexin formation in cultured cells [5][6][7] and induction of cellular protection genes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of H 2 O 2 in the plant in response to herbivory, before any subsequent secondary pathogen invasion, could be advantageous because timing of the induction of defense responses can be an important factor in the success or failure of plants to defend against pathogen attacks (Dangl et al, 1996), and wound-generated H 2 O 2 that occurs in the veins also could have a defensive role against bacteria, fungi, or viruses, as they may invade leaves wounded by herbivores (Orozco-Cárdenas and Ryan, 1999). ROS also represent second messengers that eventually activate downstream defense reactions (Foyer and Noctor, 2005), such as synthesis of pathogenesis-related proteins (Chen et al, 1993), glutathione S-transferase, glutathione peroxidase (GPX), and ubiquitin (Levine et al, 1994), as well as phytoalexin accumulation (Devlin and Gustine, 1992;Mithöfer et al, 2004) and production of herbivoreinduced volatile products (Mithöfer et al, 2004).…”
mentioning
confidence: 99%